2021
DOI: 10.1002/hep.31548
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate and Potentially Inappropriate Medication Use in Decompensated Cirrhosis

Abstract: Background and Aims Patients with decompensated cirrhosis are prescribed numerous medications. Data are limited as to whether patients are receiving medications they need and avoiding those they do not. We examined a large national claims database (2010‐2015) to characterize the complete medication profile as well as the factors associated with appropriate and potentially inappropriate medication use in 12,621 patients with decompensated cirrhosis. Approach and Results Clinical guidelines and existing literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 24 publications
1
29
1
1
Order By: Relevance
“…(11,22) These metrics are unlikely to benefit from further intervention. In contrast, Kardashian et al also found that 2% of patients with recent variceal hemorrhage underwent timely repeat procedures for variceal obliteration, and Thomson et al (20) showed that, although many patients received β-blockade, most did not refill their medication. (11)…”
Section: Quantifying Performance Gapsmentioning
confidence: 97%
“…(11,22) These metrics are unlikely to benefit from further intervention. In contrast, Kardashian et al also found that 2% of patients with recent variceal hemorrhage underwent timely repeat procedures for variceal obliteration, and Thomson et al (20) showed that, although many patients received β-blockade, most did not refill their medication. (11)…”
Section: Quantifying Performance Gapsmentioning
confidence: 97%
“…While a relevant number of patients were not treated according to current guidelines depending on the underlying decompensating event, adherence was numerically higher in the German primary care population when compared to a recently published US cohort [4]. Notably, the use of opioids was numerically lower, with 9.5 % in the German cohort vs. 53.2 % in the US cohort, while NSAIDs, benzodiazepines, and PPIs prescription showed similar numbers.…”
Section: Discussionmentioning
confidence: 79%
“…Evidence-based pharmacological interventions that have an established benefit in secondary prophylaxis are recommended by international guidelines and published by the respective medical societies [2,3]. A recent analysis of large claims databases in the United States (US) suggested that adherence to guideline recommendations for secondary prophylaxis in patients after a first decompensation event is limited [4]. This is likely to affect the recurrence rates of the decompensating event, increase costs from repeated hospital admissions, and worsen the patient's overall prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Ascites were the most common complication of cirrhosis (86.5%), followed by hepatic encephalopathy (37.8%), variceal bleeding (17.5%), HRS (6.3%), and SBP (6.1%). 24 Rifaximin was introduced to treat hepatic encephalopathy by reducing ammonia via regulation of the gut microbiome. Dong et al 25 reported that long-term rifaximin treatment reduced the rate of AKI in cirrhosis patients.…”
Section: Discussionmentioning
confidence: 99%